The Need for Software Project Monitoring Methodology: An Exploratory Survey at Malaysian Public Sector (International Journal of Innovative Computing, 2014)
Information Communication Technology (ICT) isone of the enabler for the Malaysian transformation programs.Malaysian Public Sector has formed many ICT strategies that inline with Malaysian transformation programs. Under theenrichment of ICT, many software projects are planned anddeveloped for the Malaysian Public Sector. Successfulimplementations of software projects are addressed as one of theimportant foundations that support Malaysian transformationprograms especially at the Public Sector of Malaysia. Thus, it isimportant to make sure that these ICT projects are successfullyexecuted. Therefore, monitoring and controlling softwareprojects are the basic disciplines to ensure the success of anysoftware projects. The aim of this paper is to investigate the needof software project monitoring methodology for MalaysianPublic Sector. In this paper, we deliver insights from thepractitioner’s perspectives on software projects monitoring at theMalaysian Public Sector through an exploratory survey. Thesurvey findings indicated that there is a need for softwareprojects monitoring methodology at Malaysian Public Sector.This paper also identifies 10 important factors that contributingto successful software projects at Malaysian Public Sector.